Social networking relationships, firm‐specific managerial experience and firm performance in a transition economy: A comparative analysis of family owned and nonfamily firms - Acquaah, Moses (Strategic Management Journal, 2012)
Abstract The effect of social networking relationships, firm‐specific managerial experience, and their interactions on performance between family owned and nonfamily firms are studied. Using data from 106 organizations in Ghana, the findings show that family owned firms benefit more from networking relationships with bureaucratic officials than do nonfamily firms. However, nonfamily firms benefit more from networking relationships with community leaders and firm‐specific managerial experience than do family owned firms. Networking relationships with politicians impede performance for nonfamily firms. Nonfamily firms are better able than family owned firms to use their firm‐specific managerial experience to manage the resources and capabilities obtained from networking relationships with community leaders to create value. Moreover, firm‐specific managerial experience attenuates the detrimental effects of networking with politicians for both types of firms. Copyright © 2012 John Wiley & Sons, Ltd.